Generational accounting : theory and application - Bonin, Holger, 1968- (Berlin ; New York : Springer, 2001)
Among the concepts used to assess the sustainability of fiscal policy in a changing demographic environment, generational accounting has become the most prominent. The book is an indispensable source of reference for analysts employing generational accounting and for those wishing to study intertemporal redistribution through fiscal policy.
1. The Rationale for Generational Accounting.- 2. Net Taxes of Living Generations.- 3. The Intertemporal Public Budget.- 4. Assessing Fiscal Imbalance.- 5. The Intertemporal State of German Public Finances.- 6. Immigration Policy and Fiscal Sustainability.- 7. Options for Social Security Reform.- 8. Whither Generational Accounting?.- A. Appendix: Proofs.- A.1 Separability of Generational Accounts.- A.2 Invariance of the Relative Fiscal Imbalance.- A.3 Normal Reaction of Future Generational Accounts.- B. Appendix: The Demographic Model.- C. Appendix: German Public Sector Budgets.- References.
Keywords: Generational accounting